PENINGKATAN HASIL BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN CANVA DI KELAS IV SDN 24 PARUPUK TABING KOTA PADANG - Aini, Sri; Reinita; Ladiva, Hasmai Bungsu; Wahyuni, Etri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the improvement of learning outcomes in Pancasila Education through the implementation of the Problem Based Learning model assisted by Canva media in Grade IV of SDN 24 Parupuk Tabing, Padang City. This research is a Classroom Action Research (CAR) employing both qualitative and quantitative approaches. The subjects of the study were 24 students.The results of the study indicate improvements in: (a) lesson planning, where in Cycle I the average score was 89.55% (B) and increased to 95.83% (SB) in Cycle II; (b) the teacher aspect, where in Cycle I the average score was 87.49% (B) and increased to 92.85% (SB) in Cycle II; (c) the student aspect, where in Cycle I the average score was 87.49% (B) and increased to 92.85% (SB) in Cycle II; and (d) student learning outcomes, where in Cycle I the average score was 80.52% (B) and increased to 91.56% (SB) in Cycle II.Thus, it can be concluded that the Problem Based Learning model assisted by Canva media can improve students’ learning outcomes in Pancasila Education.